Life assessment of penstock based on stress and flow analysis: A case study of Trishuli hydropower station - Koirala, Sushil; Acharya, Suman (Journal of Innovations in Engineering Education, 2026)
Hydropower penstocks are subjected to structural degradation due to internal pressure and wall thickness reduction over a period of time. This research presents a combined numerical and analytical assessment of a penstock located upstream of the Main Inlet Valve of an operating plant, Trishuli Hydropower Station (24 MW). The net hydraulic head is calculated considering surging head, frictional head, bend loss, and reducer loss. Based on net hydraulic head, internal pressure was analytically calculated and validated through Computational Fluid Dynamics. Structural behavior was determined analytically, calculating the Von Mises Stress and confirmed through the Finite Element Method in ANSYS. Mesh independent test was performed for numerical reliability. The critical thickness was calculated to be 5.537 mm analytically, whereas through numerical simulation it was found to be 5.3 mm, showing a deviation of 4.28 %. The Ultrasonic Testing performed on the penstock shows the reduction of wall thickness from 12 mm to 7.5 mm, indicating the corrosion rate of 0.078 mm/year. As per the projection, the penstock reaches its critical thickness by 2050, showing the estimated safe remaining service life is approximately 25 years from 2025 AD.